Red alert [compact disc, unabridged] : an NYPD Red mystery - Patterson, James, 1947-; Karp, Marshall (Patterson, James, 1947- NYPD red mystery., 2018)
When a fundraiser involving New York's wealthy elite is targeted by a fatal blast, detectives Zack Jordan and Kylie MacDonald discover a link between the bombing and the murder of a high-profile woman filmmaker before realizing that the bombers may be among the A-list guests they were hired to protect.